Erratum: Comprehensive proteome expression profiling of undifferentiated versus differentiated neural stem cells from adult rat hippocampus - Maurer, Martin H.; Feldmann, Robert Enrico; Fütterer, Carsten Dietmar; Butlin, Jo; Kuschinsky, Wolfgang (Neurochemical research, 2005)
Adult neural stem cells can be isolated from various regions of the rat brain and seem to have multilineage differentiation potential. In this study, we investigated the hypothesis that global protein expression of adult neural stem cells isolated from rat hippocampus is changed during in vitro differentiation. After 2 days of differentiation, we separated total protein extracts by two-dimensional gel electrophoresis and used mass spectrometry and gel-matching for identification. We detected a differential expression in 367 regulated protein spots, of which 128 could be identified. Regulated proteins included participants in transcription and DNA metabolism; signal transduction and Ca2+-signaling; MAP kinase pathways; cytoskeletal rearrangement; regulation of cell cycle, proliferation, and survival; protein biosynthesis, folding, and degradation; and glycine and glutamate metabolic pathways. These results suggest a massive reorganization of the stem cell proteomic profile upon differentiation and indicate potential cellular targets mediating the differentiation of neural stem cells.